Regelmäßiger Wechsel von Fraß- und Flugjahren bei Thaumetopoea pinivora Treitschke schon seit mindestens 1910 bekannt (Lepidoptera: Thaumetopoeidae). - Hering, Friedrich (Contributions to Entomology = Beiträge zur Entomologie, 1968)
Since Koch’s studies on the biology of Thaumetopoea pinivora Treitschke agree with the author’s own observations covering half a century, and the seeming exceptions can be sufficiently explained by pupae developing in the second year, the generation problem of Thaumetopoea pinivora Treitschke can finally be shelved.